2019
DOI: 10.1002/ecy.2655
|View full text |Cite
|
Sign up to set email alerts
|

Lianas have a seasonal growth advantage over co‐occurring trees

Abstract: The seasonal growth advantage hypothesis posits that plant species that grow well during seasonal drought will increase in abundance in forests with increasing seasonality of rainfall both in absolute numbers and also relative to co‐occurring plant species that grow poorly during seasonal drought. That is, seasonal drought will give some plant species a growth advantage that they lack in aseasonal forests, thus allowing them attain higher abundance. For tropical forest plants, the seasonal growth advantage hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
61
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 53 publications
(69 citation statements)
references
References 64 publications
(159 reference statements)
5
61
1
2
Order By: Relevance
“…) are consistent with Schnitzer (), who also found that lianas grew more than trees when water was limited. Similarly, in a recent study of >1,100 canopy trees and >800 canopy lianas in central Panama, Schnitzer and van der Heijden () reported that liana growth rate was higher during the dry season than the wet season in each of the five years of their study, and that lianas grew as much during the ~4‐month dry season as they did during the ~8‐month wet season. By contrast, they found that tree growth rate was far higher during the wet season, and that trees grew far more during the 8‐month wet season than the 4‐month dry season.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…) are consistent with Schnitzer (), who also found that lianas grew more than trees when water was limited. Similarly, in a recent study of >1,100 canopy trees and >800 canopy lianas in central Panama, Schnitzer and van der Heijden () reported that liana growth rate was higher during the dry season than the wet season in each of the five years of their study, and that lianas grew as much during the ~4‐month dry season as they did during the ~8‐month wet season. By contrast, they found that tree growth rate was far higher during the wet season, and that trees grew far more during the 8‐month wet season than the 4‐month dry season.…”
Section: Discussionmentioning
confidence: 79%
“…For example, in a seasonal forest in Panama, understory lianas were found to grow in height seven times more than understory trees during the dry season, but only two times more during the wet season (Schnitzer ). In a more recent and much larger study in Panama, canopy lianas had a far higher growth rate during the dry season than the wet season, whereas trees had the opposite pattern, with a higher growth rate during the wet season than the dry season (Schnitzer and van der Heijden ).…”
Section: Introductionmentioning
confidence: 95%
“…Lianas may also sustain their water potential by either accessing deeper water (Andrade et al, ; Chen et al, ) or different water sources (De Deurwaerder et al, ) than trees or by exercising strong stomatal control under drought conditions. Lianas may therefore have the ability to remain photosynthetically active during periods of seasonal drought (Cai et al, ; Sánchez‐Azofeifa et al, ; Schnitzer, ), thereby taking advantage of the increase in irradiance as a result of reduced cloud cover during the dry season (Graham, Mulkey, Kitajima, Phillips, & Wright, ; Schnitzer, ) to vigorously grow (Schnitzer & van der Heijden, ). However, even though liana biomass increment during the dry season was greater than during the wet season in all 5 years (Figure ), the relative impact of lianas on tree biomass increment did not differ between the seasons (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…Rowland et al, ). We did not include a shrinkage correction for liana stems for two reasons: (a) liana stems were measured with diameter tapes which have an accuracy of 1 mm and shrinkage terms were therefore considerably inflated compared to shrinkage calculated from the tree dendrometer measurements, and (b) liana stems generally grew faster in the dry than in the wet season (Schnitzer & van der Heijden, ) and adding any shrinkage correction would amplify any differences in liana growth between the dry and the wet season. By not correcting liana diameter measurements for shrinkage effects, we therefore present a more conservative pattern in seasonal differences in liana biomass increment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation